Dinamika dalam Kepemimpinan Desa : Studi pada Rektrumen Aparatur Desa, di Desa Weseben Kabupaten Malaka - Sarci Aurelia Tibultali; Yeftha Yerianto Sabaat; Diana S.A Natalia Tabun; Frans B.R Humau (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study, entitled "Dynamics in Village Leadership (A Study of Village Apparatus Recruitment in Weseben Village, Malaka Regency)," aims to analyze the leadership style of village heads in the apparatus recruitment process, uncover the growing practices of patronage and clientelism, and examine their implications for the implementation of good governance principles at the village level. Theoretically, this research is based on village leadership theory, patronage-clientelism theory, and the concept of good governance, which emphasizes the values ​​of transparency, accountability, and public participation in village governance.The method used was a qualitative approach with a case study design. Data were collected through in-depth interviews with village heads, village officials, traditional leaders, members of the Village Consultative Body (BPD), and the community, and was supported by field observations and documentation studies. The results indicate that: (1) the leadership style of village heads in Weseben is dominant and personalistic, with the village head retaining full control over the apparatus recruitment process, (2) apparatus recruitment places greater emphasis on loyalty and personal closeness than on professional competence, (3) The practice of patronage and clientelism is strongly evident in the relationship between the village head as patron and village officials as clients, which is built through kinship ties and reciprocal interests, (4) decisions regarding the appointment of officials are often tinged with elements of nepotism and collusion to strengthen the village head's political support base, and (5) the recruitment system is not yet oriented towards the principle of a merit system, namely a selection system based on individual ability, achievement, and integrity, as implemented in professional governance.Thus, it can be concluded that the dynamics of village leadership in Weseben are still strongly influenced by the practice of patronage and clientelism, which hinders the realization of democratic, transparent, and accountable village governance.